Biodiversidad marina de Costa Rica, los microcrustáceos: Subclase Copepoda (Crustacea: Maxillopoda) - Morales-Ramírez, Alvaro (2001)
This report is part of a series that summarizes the species and localities of Costa Rican marine taxa. A review of the literature on copepods, both pelagic and benthic for the Pacific and Caribbean coast of Costa Rica, includes eigthy species. Sixty seven pelagic species have been found, distributed between sixteen calanoid, one cyclopoid, three harparticoid and four poecilostomatoid families. Moreover, thirteen benthonic species distributed into six families, all harparticoids, are reported. Among the pelagic families, Pontellidae has six species, while Paracalanidae and Eucalanidae had five each. Other families, like Calanidae, Pseudodiaptomidae and Acartiidae had four species and most families only one. Forty five species are reported only for the Pacific coast, thirteen for the Caribbean coast, only nine species occurred in both coasts; being a direct consequence of the more intensive research effort in the Pacific. Pelagic copepod biodiversity reflects different oceanographic conditions in both coasts.Typical estuarine species were found in the lower region of the Gulf of Nicoya, while a mixture of estuarine and oceanic species were found in Golfo Dulce. Diversity in the Caribbean, specially at the Cahuita coral reef is lower in comparison with the copepod diversity found in other regions in the Caribbean sea. This may be due to the high sediment resuspension rate characteristic of the Cahuita coral reef, which could affect the reproduction of many holozooplankters, specially copepods. Although sixty seven pelagic copepod species appears to be in low numbers, in terms of specific biodiversity it is as high when compared to numbers found in other tropical areas. Thirteen species are reported in the literature, all harparticoids. Five species, three sub-species and one genera were new to science. Balacopsylla is reported for the first time from a neotropical regions, while the genus Karllangia, represented by two coexisting species in the Caribbean coast, belong to a few circumtropical-subtropical genera. The most diverse family was Tetragonicipitidae. This is the first effort to summarize the available information about the biodiversity of marine copepods for Costa Rica’s coasts.